The Degree to Which Career Education Teachers are Practicing the Knowledge Economy skills, as Perceived by the Educational Supervisors in Jordan - Al-Tweissi , Ahmed (Jordan Journal of Educational Sciences, 2014)
Ahmed Issa Al-Tweissi , Mutah University-Jordan. Abstract: This study aimed at determining the degree to which the Career education teachers are practicing the knowledge economy skills as perceived by their educational supervisors. The study sample consisted of (62) supervisors, with the percentage of 71% of the entire population. A self-completed questionnaire was developed for the purpose of this study, it consisted of 64 items distributed on nine domains, and its reliability and validity were verified. The results of the study revealed the following: 1) The mean score for the degree of practicing knowledge economy skills by Career education teachers was 2.96, and this indicates the degree of moderate practices. 2) The means of knowledge economy skills domains were ranked respectively, from the best to the worst practices, as follow: communication and interaction with the students, leadership and management, personal, career guidance and counseling, academic, evaluation and school tests, creativity and innovation, professional development, and finally information and communications technology skills. 3) There were no statistically significant differences due to the impact of the variable of supervisors' educational qualification, whereas, there were differences that can be attributed to the variable of supervisors' experience, and in favor of those supervisors with recent experience in educational supervision. 4) There were an interaction between the variables of the study, with the value of P= 6.480 and the significance level of (0.003). Based upon the above briefed findings several recommendations were proposed, including the necessity to pay more attention to the professional development programs for Career education teachers in Jordan, with special focus on the domain of information and communication technology.